Coherent Control of Molecular Dissociation by Selective Excitation of Nuclear Wave Packets - López Peña, Hugo A.; Shusterman, Jacob M.; Ampadu Boateng, Derrick; Lao, Ka Un; Tibbetts, Katharine Moore (Frontiers in Chemistry, 2022)
We report on pump-probe control schemes to manipulate fragmentation product yields in p-nitrotoluene (PNT) cation. Strong field ionization of PNT prepares the parent cation in the ground electronic state, with coherent vibrational excitation along two normal modes: the C-C-N-O torsional mode at 80 cm-1 and the in-plane ring-stretching mode at 650 cm-1. Both vibrational wave packets are observed as oscillations in parent and fragment ion yields in the mass spectrum upon optical excitation. Excitation with 650 nm selectively fragments the PNT cation into C7H7+, whereas excitation with 400 nm selectively produces C5H5+ and C3H3+. In both cases the ion yield oscillations result from torsional wave packet excitation, but 650 nm and 400 nm excitation produce oscillations with opposite phases. Ab initio calculations of the ground and excited electronic potential energy surfaces of PNT cation along the C-C-N-O dihedral angle reveal that 400 nm excitation accesses an allowed transition from D0 to D6 at 0˚ dihedral angle, whereas 650 nm excitation accesses a strongly allowed transition from D0 to D4 at a dihedral angle of 90˚. This ability to access different electronic excited states at different locations along the potential energy surface accounts for the selective fragmentation observed with different probe wavelengths. The ring-stretching mode, only observed using 800 nm excitation, is attributed to a D0 to D2 transition at a geometry with 90˚ dihedral angle and elongated C-N bond length. Collectively, these results demonstrate that strong field ionization induces multimode coherent excitation and that the vibrational wave packets can be excited with specific photon energies at different points on their potential energy surfaces to induce selective fragmentation.